Pengembangan Aplikasi Pengelolaan Penyimpanan dan Distribusi Barang berbasis Web (Studi Kasus : PT. Harrasima Inventory Logistic) - Aulia Rizki Ananda; Agi Putra Kharisma; Issa Arwani (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2021)
PT. Harrasima Inventory Logistics, has warehouses spread throughout Indonesia that function to store and distribute network modules to all operational areas of cooperating providers. To monitor, record, and manage the process of storing, distributing and repairing module, the warehouse still use manual recording. This method is less effective when stakeholders such as Customers, Supervisors, FSL, Project Managers and Callcenters want to know the availability of modules in the warehouse or the warehouse data cannot be seen in real time. One way that can be used to overcome this problem is to create a system or web-based application that can take inventory handling, inventory recording, inventory processing and module data reporting in the warehouse. This writing aims to design and build a web-based distribution and storage management application for PT. Harrasima Inventory Logistics using the waterfall method. From the requirement analysis of the distribution and storage management application of PT. Harrasima Inventory Logistic produces 145 functional requirements, 1 non-functional requirement and 14 actors. From the results of the requirement analysis 57 functional requirements were designed from 145 functional requirement, a design was made which resulted in 4 controller classes, 17 model classes on the system architecture and 42 entities on the system data structure. The results of unit testing, integration testing, and validation testing of the system show 100% valid while the results of the usability test of the system get an average value of 75.57692 with the predicate Excellent.